Techno-economic evaluation of CO2-rich natural gas dry reforming for linear alpha olefins production. (1st February 2020) - Chen, Qianqian; Wang, Danfeng; Gu, Yu; Yang, Sheng; Tang, Zhiyong; Sun, Yuhan; Wu, Qing
Highlights: 500, 000 ton/a of hydrocarbon alcohols production plant is evaluated. CO2 -rich natural gas dry reforming coupled with FTO process is designed. Aspen model of the integrated system for linear alpha olefins production is built. Techno-economic performance of the integrated system is analyzed. Abstract: The South China Sea is rich in oil and gas resources, accounting for one-third of China's total oil and gas resources. However, the natural gas there has high concentration of carbon dioxide (CO2 ), so decarbonization process is required, which will cause a large amount of energy loss and carbon emission. To realize direct, efficient and high-value utilization of CO2 -rich nature gas in the South China Sea, this paper designs a conceptual route which integrates CO2 -rich natural gas dry reforming with Fischer-Tropsch to olefins (FTO) technology to produce high value-added linear alpha olefins (LAO) products. Material and energy balance of the integrated system is calculated via Aspen Plus modelling. The energy efficiency, carbon efficiency and economic performance of this integrated system is evaluated. The results show that the net CO2 emission of this system is only 0.06 ton-CO2 /ton-product and the carbon efficiency of the system is up to 60.8%; the system's NPV is positive and much higher than zero, indicating that the system is fairly risk-resistant and economically feasible. This technical route blazes a new way for direct conversion and utilization of CO2 -rich nature gas, and has great potential for development. It not only realizes the conversion and utilization of CO2, but also produces high value-added LAO products, which will alleviate the shortage of LAO production in China.